TEORI RELATIONAL DIALECTICS DALAM KONTEKS RELASI BUDAYA JAWA - S. Rouli Manalu; Hedi Pudjo Santosa; Yanuar Luqman (Faculty of Social and Political Sciences, Universitas Diponegoro, 2007)
Theory is always formed within a specific social and cultural background. Therefore , Eastern and Western cultures are differs in the way they look at the concept of relationship. While Western theories tend to perceive relationship as the rel connections between two people or more, eastern theories consider roles, status, power, and social positions as important elements in building relationship. The main aim of this research is to implement a Relational Dialectics Theory, which is formed in the Western tradition to Javanese cultural contexts (as a part of Eastern Culture). The research’s findings indicate that some important elements in the theory are inapplicable in Javanese contexts of relationship. This phenomenon due to the domination of partiarchal ideology in the Javanese culture.